Integration of social media with targeted emails and in‐person outreach for exception from informed consent community consultation. (7th September 2021) - Hsu, Cindy H.; Fowler, Jennifer; Cranford, James A.; Thomas, Michael P.; Neumar, Robert W.
Abstract: Background: Exception from informed consent (EFIC) enables the enrollment of research subjects with emergent conditions to clinical trials without prior consent. EFIC study approval requires community consultation and public disclosure. We hypothesized that the integration of social media with targeted emails and in‐person outreach is an effective community consultation strategy. Methods: We utilized social media with targeted emails and in‐person outreach for the community consultation of the ACCESS cardiac arrest trial. Study advertisements were disseminated using Facebook and Instagram, and targeted emails were sent to emergency medicine, prehospital, and cardiology providers. We also interviewed at‐risk individuals with cardiac conditions, their caretakers, and patient advocacy groups. Participants were asked to complete a survey about their opinions about the study. Results: We collected 559 surveys over an 8‐week period, and 70.5% of the surveys were obtained using social media. The median (IQR) age of survey respondents was 44 (33‐57) years; 89.9% were White and 60.1% were women. A total of 91.3% believed ACCESS was an important study. Compared to the in‐person group, more from social media (81.8% vs. 63.3%, p < 0.05) and targeted email (77.4% vs. 63.3%, p < 0.05) groups said they would include their loved ones in the study. More from the in‐person group believed that their opinion would be considered seriously compared to the social media (75.9% vs. 62.6%, p < 0.05) and targeted email (75.9% vs. 54.5%, p < 0.05) groups. The incorporation of social media and targeted emails for community consultation reduced the cost per survey by fourfold compared to an in‐person–only strategy. Conclusions: The integration of social media with targeted emails and in‐person outreach was a feasible and cost‐saving approach for EFIC community consultation. Future work is necessary to determine the perception and best utilization of social media for community consultation.